Análise da expressão do TFDP1 no endométrio tópico de mulheres com endometriose - Jibrim, Rodrigo Lopes Meime [UNIFESP] (2016)
Introduction: one of the researches fields of the ethiopathogenesis of endometriosis aims to identify endometrial disorders as the origin of the disease. Changes in expression of proteins related to cell adhesion, collagenases, and mainly of the cell cycle regulators have been identified. Based on these previous studies we set out to analyze the expression of TFDP1 gene in the endometrium of women with endometriosis. This gene, member of the E2F family encodes several proteins responsible for the control of passage between the G1 and S phase of the cycle, key point of regulation of cell division. Proposition: to evaluate, using Real Time PCR, TFDP1 gene expression in endometrial cells in culture, of women with endometriosis. Methodology: five samples were studied from the endometrium of healthy patients (no pelvic disease determined by means of laparoscopy for tubal ligation) and six patients with diagnosis of deep endometriosis done during surgery. The samples, from the Bank of cells of Endometriosis Unit-UNIFESP, were subjected to PCR-Real Time processing. The results were expressed through the fold and Ct. Results: we observed higher expression of TFDP1 in the cells of women with endometriosis (ct 32,08) when compared with the control group (ct 29,019) (p < 0 .05). And a fold of -2.04674 in the control group compared to the endometriosis (t test 0.01059). Conclusion: We found a significantly higher expression of the TFDP1 gene in the endometrium of women with endometriosis when compared to the same tissue of healthy women.